Positive Synergistic Effects of Quercetin and Rice Bran on Human Gut Microbiota Reduces Enterobacteriaceae Family Abundance and Elevates Propionate in a Bioreactor Model - Ghimire, Sudeep; Wongkuna, Supapit; Sankaranarayanan, Ranjini; Ryan, Elizabeth P.; Bhat, G. Jayarama; Scaria, Joy (Frontiers in Microbiology, 2021)
Dietary fiber and flavonoids have substantial influence on the human gut microbiota composition that significantly impact health. Recent studies with dietary supplements such as quercetin and rice bran have shown beneficial impacts on the host alongside a positive influence of the gut microbiota. The specific bacterial species impacted by quercetin or rice bran in the diet is not well understood. In this study, we used a minibioreactor array system as a model to determine the effect of quercetin and rice bran individually, as well as in combination, on gut microbiota without the confounding host factors. We found that rice bran exerts higher shift in gut microbiome composition when compared to quercetin. At the species level, Acidaminococcus intestini was the only significantly enriched taxa when quercetin was supplemented, while 15 species were enriched in rice bran supplementation and 13 were enriched when quercetin and rice bran were supplemented in combination. When comparing the short chain fatty acid production, quercetin supplementation increased isobutyrate production while propionate dominated the quercetin and rice bran combined group. Higher levels of propionate were highly correlated to the lower abundance of the potentially pathogenic Enterobacteriaceae family. These findings suggest that the combination of quercetin and rice bran serve to enrich beneficial bacteria and reduce potential opportunistic pathogens. In vivo studies are necessary to determine how this synergy of quercetin and rice bran on microbiota impact host health.